2017
DOI: 10.1002/er.3819
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and analysis of hydrogen and electricity production from a Generation IV lead-cooled nuclear reactor integrated with a copper-chlorine thermochemical cycle

Abstract: SummaryAn integrated system for compressed hydrogen and electrical power production based on a Generation IV nuclear reactor (a lead-cooled reactor) is proposed.The hydrogen is produced by the integrated system through a hybrid thermochemical and electrical water decomposition cycle. The water decomposition cycle is based on copper and chlorine compounds and decomposes water through four main steps. The electrical power is produced by the Rankine cycle, which also contributes to cooling the compressed hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…The lower operating temperature (approximately 530°C) and high efficiency (approximately 43%) of Cu–Cl thermochemical cycle and less stringent requirement for materials of construction as compared with those of S‐I cycle improves the prospects for scaling up and hydrogen production at commercial scale . Also, because of its lower temperature requirements, the Cu–Cl cycle can be more readily combined with solar, geothermal, or waste heat sources . This cycle in tandem with most of the Generation IV nuclear reactors (based on molten salts or supercritical water) may serve as a suitable candidate for accomplishment of NGNP‐NHI (Next Generation Nuclear Plant‐Nuclear Hydrogen Initiative).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower operating temperature (approximately 530°C) and high efficiency (approximately 43%) of Cu–Cl thermochemical cycle and less stringent requirement for materials of construction as compared with those of S‐I cycle improves the prospects for scaling up and hydrogen production at commercial scale . Also, because of its lower temperature requirements, the Cu–Cl cycle can be more readily combined with solar, geothermal, or waste heat sources . This cycle in tandem with most of the Generation IV nuclear reactors (based on molten salts or supercritical water) may serve as a suitable candidate for accomplishment of NGNP‐NHI (Next Generation Nuclear Plant‐Nuclear Hydrogen Initiative).…”
Section: Introductionmentioning
confidence: 99%
“…14 Also, because of its lower temperature requirements, the Cu-Cl cycle can be more readily combined with solar, geothermal, 15 or waste heat sources. 16 This cycle in tandem with most of the Generation IV nuclear reactors (based on molten salts or supercritical water) may serve as a suitable candidate for accomplishment of NGNP-NHI (Next Generation Nuclear Plant-Nuclear Hydrogen Initiative). In addition, this cycle shows better hydrogen and oxygen generation kinetics and higher efficiency.…”
mentioning
confidence: 99%
“…Activities related to hydrogen production and distribution have already been initiated by many advanced countries, and they have developed their own systems for this purpose. The most relevant to the current study includes an integration system for hydrogen and electricity production from Gen IV nuclear reactors (lead cooled and super critical water cooled nuclear reactors [SCWR]) . These studies were supported by detailed energy and exergy analyses and applied a copper chlorine (Cu–Cl) coupled cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant to the current study includes an integration system for hydrogen and electricity production from Gen IV nuclear reactors (lead cooled and super critical water cooled nuclear reactors [SCWR]). 5,6 These studies were supported by detailed energy and exergy analyses and applied a copper chlorine (Cu-Cl) coupled cycle. This research assessed various nuclear power plants and concluded that HTGR was the feasible option based on technical and economic analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sayyaadi and Boroujeni indicated a thermal efficiency improvement of the 5‐step Cu‐Cl thermochemical cycle by using an optimization algorithm and a heat exchanger network (HEN). Al‐Zareer et al proposed a novel system integration by using a combination of the 5‐step Cu‐Cl thermochemical cycle, a nuclear reactor, a combined cycle, and a hydrogen compression system, to carry out the cogeneration of compressed hydrogen and electricity where the overall energy and exergy efficiencies were found to be 25.4% and 40.6%, respectively . Notably, the overall energy efficiency of the integrated system decreases by using Rankine cycle.…”
Section: Introductionmentioning
confidence: 99%